In vitro immunomodulation for enhancing T cell–based diagnosis of Mycobacterium tuberculosis infection - Slater, Madeline; Tran, Minh-Chi; Platt, Lauren; Luu, Lien T.; Phan, Ha T.; Pham, Phuong T.; Do, Tam B.; Nguyen, Hanh T.; Gaur, Rajiv L.; Parsonnet, Julie; Cattamanchi, Adithya; Luo, Robert; et al. (Diagnostic microbiology and infectious disease, 2015)
Interferon-gamma release assays have limited sensitivity for detecting latent tuberculosis infection. In this study, we determine if the addition of immunomodulators to the QuantiFERON-TB Gold In-Tube (QFT-GIT) increased test sensitivity without compromising specificity. We prospectively compared QFT-GIT results with and without incubation with 2 immunomodulators (lipopolysaccharide [LPS] and polyinosine-polycytidylic acid [PolyIC]) in 2 cohorts—113 culture-confirmed tuberculosis (TB) subjects in Hanoi, Vietnam, and 226 documented QFT-GIT–negative, low TB risk health care workers undergoing annual TB screening at a US academic institution. Sensitivity of the tests in TB subjects was 84.1% with the standard QFT-GIT and 85.8% and 74.3% after incubation with LPS and PolyIC, respectively. Specificity in low TB risk health care workers was 100% with the standard QFT-GIT by design and 86.7% with LPS and 63.3% with PolyIC. In conclusion, use of the 2 immunomodulators did not improve sensitivity of the QFT-GIT in TB patients and reduced specificity in low-risk health care workers.